Country of Origin Effect and Animosity on The Attitude and Purchase Intention of Foreign Products - Ramadania, Ramadania; Gunawan, Sri; Jamaliah, Jamaliah (ASEAN Marketing Journal, 2021)
The purpose of this study is to examine COO effect and Animosity on the attitude and purchase intention of foreign products in ethnic subculture within a country. This research is tested in Malay and Chinese ethnic subculture in West Kalimantan, Indonesia. The categories of product are foods from Malaysia. Sample in this study is 435 respondents, consists of 218 Malay respondents from Ma-lay and 217 Chinese respondents. The collection of data was using non probability sampling method by combining accidental and snowball sampling. Data analysis uses structural equation modeling (SEM) Multi-group.The results show that, there is a positive influence of COO on attitudes of foreign products for both Malay and Chinese ethnic. This study also show that, the influence of COO on the purchase intentions of foreign products can only be proven in Chinese ethnic. Furthermore, the results show that animosity have a negative influence on attitude toward foreign products. In addition, attitude also have a positive influence on the intention to purchase. However, this study fails to prove the influence of animosity on the intention to purchase of foreign products. These results indicate that there are differences in consumer behavior between Malay and Chinese ethnic in the evaluation of foreign products.